2015
DOI: 10.1002/cctc.201402996
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Primary Amines by Reductive Amination of Ketones with Ammonia over Supported Pt catalysts

Abstract: Supported platinum catalysts are studied for the reductive amination of ketones under ammonia and hydrogen. For a model reaction with 2-adamantanone, Pt-loaded MoO x /TiO 2 (Pt-MoO x /TiO 2 ) shows the highest yield of primary amine. The catalyst is effective for the selective transformation of various aliphatic and aromatic ketones to the corresponding primary amines, which demonstrates the first example of the selective synthesis of primary amines by this reaction. The yield of the amine increases with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
68
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 27 publications
0
68
0
Order By: Relevance
“…In our previous IR study of the pyridine adsorbed on these catalysts, we showed that Pt–MoO x /TiO 2 , Pt/TiO 2 , and Pt/Al 2 O 3 were Lewis acidic owing to the exposed cations on the support surface . Also, we reported that the C=O stretching band in the IR spectrum of the acetone coordinated to the Mo n + Lewis acid sites on Pt–MoO x /TiO 2 was observed at lower wavenumbers than Pt/TiO 2 and Pt/Al 2 O 3 . The IR spectra of acetone on these catalysts are shown in Figure A; the spectra at t= 0 s are a result of the acetone adsorbed on the catalyst at 40 °C after adsorption of acetone followed by purging with He flow for 10 min.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…In our previous IR study of the pyridine adsorbed on these catalysts, we showed that Pt–MoO x /TiO 2 , Pt/TiO 2 , and Pt/Al 2 O 3 were Lewis acidic owing to the exposed cations on the support surface . Also, we reported that the C=O stretching band in the IR spectrum of the acetone coordinated to the Mo n + Lewis acid sites on Pt–MoO x /TiO 2 was observed at lower wavenumbers than Pt/TiO 2 and Pt/Al 2 O 3 . The IR spectra of acetone on these catalysts are shown in Figure A; the spectra at t= 0 s are a result of the acetone adsorbed on the catalyst at 40 °C after adsorption of acetone followed by purging with He flow for 10 min.…”
Section: Resultsmentioning
confidence: 90%
“…The IR spectra of acetone on these catalysts are shown in Figure A; the spectra at t= 0 s are a result of the acetone adsorbed on the catalyst at 40 °C after adsorption of acetone followed by purging with He flow for 10 min. The C=O stretching band of acetone for Pt–MoO x /TiO 2 is at a lower wavenumber (1690 cm −1 ) than those for Pt/TiO 2 (1709 cm −1 ) and Pt/Al 2 O 3 (1703 cm −1 ), which indicates that the Lewis acid sites on Pt–MoO x /TiO 2 weakens the C=O bond strength more effectively than those on Pt/TiO 2 and Pt/Al 2 O 3 . Then, we studied the reactivity of the acetone on these catalysts under 1 atm H 2 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…So far, metal complex‐based homogeneous catalysts, such as Rh, Ru, and Ir‐based complexes and heterogeneous catalysts such as Pt, Ru, Rh, Pd, Ni, Co, and Cu have been reported for the reductive amination of carbonyl compounds with ammonia and hydrogen. However, the selectivity to primary amines in reductive amination remains difficult to control because primary amines are more nucleophilic than ammonia and easily react with aldehydes to form secondary amines . In addition, undesired hydrogenation of the carbonyl groups and the unsaturated bonds also limit the selectivity to corresponding primary amines .…”
Section: Introductionmentioning
confidence: 99%